CONCEPT AND LEGALITY OF FRANCHISE BUSINESS MODEL IN FIQH MUAMALAH - Hidayatul Akbar (Al-Mudharabah: Jurnal Ekonomi dan Keuangan Syariah, 2024)
Franchising is one type of marketing in the modern era, where an individual businessman or business entity claims his business with certain characteristics and has special rights or the use of trademarks and business models. This research wants to see about the concept and legality of the franchise business model in the perspective of Islamic economic law. This research uses a literature approach, where the main data is obtained from secondary data sources, both from legal norms, relevant research and articles that have a relationship with this research. The results show that the concept of a business or venture using a franchise platform is permissible as long as it is in accordance with the principles allowed in Islam. Franchises are prohibited if they contain elements, such as businesses that aim to avoid various business irregularities (moral hazard), namely maysir (speculation), immorality, gharar (fraud), haram, usury, ikhtikar (hoarding/monopoly), and dharar (harmful).